Identifying reflective modes in pre-service teachers’ written reflections on the implementation of project-based learning during the school practicum - Kaldi, Stavroula; Zafeiri, Stella (Frontiers in Education, 2023)
The study deals with the written reflection about the implementation of project-based learning (PjBL) during the school practicum of final year undergraduate pre-service teachers . The research focuses on highlighting participant undergraduate pre-service teachers’ meaning through reflexive thematic analysis (Braun & Clarke, 2019) and modes of expressing positions - according to the model suggested by Yesilbursa (2011) - toward the implementation of child-centred instructional approaches such as Pj-BL. The research methodology identified prospective teachers’ positive points, concerns and challenges when applying Pj-BL. The findings also indicate that prospective teachers need to develop further their reflective thinking skills to providing explanations, solutions and areas of personal improvement while they produce written reflective reports.